Reverse Address Resolution Protocol (RARP) - Sehrawat, Mr Rahul; Gupta, Mr Pankaj; Yadav, Mr Ravishu (IJRDO -Journal of Computer Science Engineering, 2015)
The Reverse Address Resolution Protocol (RARP) is an obsolete computer networking protocol used by a clientcomputer to request its Internet Protocol (IPv4) address from a computer network, when all it has available is its Link Layer orhardware address, such as a MAC address. The client broadcasts the request, and does not need prior knowledge of the networktopology or the identities of servers capable of fulfilling its request. RARP is described in Internet Engineering TaskForce (IETF) publication RFC 903. It has been rendered obsolete by the Bootstrap Protocol (BOOTP) and the modern DynamicHost Configuration Protocol (DHCP), which both support a much greater feature set than RARP. This research paper gives abrief introduction about Reverse Address Resolution Protocol (RARP) , Timing RARP Transactions ,Primary And BackupRARP Servers.